Analisis Kebermanfaatan Pelatihan Artificial Intelligence bagi Siswa Jurusan Pariwisata SMK Taman Siswa Purwokerto - Isro, Zuyinatul; Paramytha Sulistyo, Chendy Arieshanty; Prasetyowati, Henggar; Syahputri, Adilla Achmad (Universitas Negeri Gorontalo, 2025)
The rapid development of Artificial Intelligence (AI) at both national and global levels requires educational institutions, including vocational high schools, to equip students with relevant technological competencies. SMK Taman Siswa Purwokerto, as a vocational institution in Banyumas, offers study programs closely related to AI implementation, particularly in the tourism sector. Considering the positive growth of Indonesian tourism—with 13.90 million international tourist arrivals recorded in 2024—AI literacy has become essential to support digital promotion, customer service, and destination management. This community engagement program aims to provide basic AI knowledge and skills to students of SMK Taman Siswa Purwokerto while exploring their experiences, perceptions, and challenges during the training. A qualitative approach was employed through in-depth interviews, observations, and documentation. The findings indicate that AI training offers significant benefits for students, enhancing their understanding of AI applications in the tourism industry and generating recommendations for designing more industry-relevant and locally contextualized AI training.